2021
DOI: 10.1002/csr.2134
|View full text |Cite
|
Sign up to set email alerts
|

Extending the benefits of ESG disclosure: The effect on the cost of debt financing

Abstract: In recent years, greater attention has been paid to sustainability issues. Companies have received increasing pressure from stakeholders to adopt sustainable behavior and provide an adequate representation of sustainability practices. Nonfinancial disclosure has thus taken on a crucial role. In the academic field, several researchers have analyzed the effects of nonfinancial disclosure. However, limited attention has been paid to the impact of nonfinancial information on the cost of debt. This study aims at br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
190
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(205 citation statements)
references
References 88 publications
(151 reference statements)
11
190
1
3
Order By: Relevance
“…Additionally, Eliwa et al (2019) examined a sample of companies operating in 15 European countries, concluding that the impact of ESG disclosures has a negative relationship with the cost of debt. Also, Bhuiyan and Nguyen (2019) studied a sample of Australian listed companies and found a negative impact of ESG disclosures on the cost of debt (Raimo et al, 2021). The literature review shows that previous studies analyzed the impact of additional disclosures on the cost of debt.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Eliwa et al (2019) examined a sample of companies operating in 15 European countries, concluding that the impact of ESG disclosures has a negative relationship with the cost of debt. Also, Bhuiyan and Nguyen (2019) studied a sample of Australian listed companies and found a negative impact of ESG disclosures on the cost of debt (Raimo et al, 2021). The literature review shows that previous studies analyzed the impact of additional disclosures on the cost of debt.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, it can be observed that financial disclosure alone can no longer meet all the company's information needs. As a result, disclosing non-financial information about company activities, using mainly environmental, social, and sustainability reports, is becoming increasingly important (Raimo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…According to signaling theory, corporate disclosure of non-financial information broadens the spectrum of information recipients. Such practices allow companies to increase the plurality of stakeholders, from customers and employees to suppliers and government (Raimo et al, 2021;Vitolla et al, 2020) Nevertheless, managers should seek to balance the positive effects of a lower cost of capital through additional disclosures with the possible disadvantages of scope reporting (Meek et al, 1995).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature further highlights that ESG disclosures respond to societal needs (and even public pressure) in this regard (Hahn and Kühnen, 2013;Rahman and Alsayegh, 2021). It is indicated that stakeholders put increasing pressure on companies to prove that they operate sustainably, reduce negative environmental and social impacts, and implement sustainability measures (Eliwa et al, 2019;Manes-Rossi et al, 2020;Raimo et al, 2021).…”
Section: The Impact Of Esg Reporting On the Cost Of Capital: An Example Of Us Healthcare Entities 682mentioning
confidence: 99%
“…From the perspective of the legitimacy theory, ESG disclosure (ESGD) mitigates firm-specific risks [4], which at least theoretically, should help to reduce their weighted average cost of capital, thereby improving firm performance (FP). Using data from international listed firms belonging to the S&P 1200 Global Index, Raimo, Caragnano, Zito, Vitolla, and Mariani [5] find a negative relation between ESGD and the cost of debt. Similarly, Raimo, de Nuccio, Giakoumelou, Petruzella, and Vitolla [6] evidence a negative relationship between ESGD and the cost of equity capital among international listed firms operating in the food and beverage sector.…”
Section: Introductionmentioning
confidence: 99%